Geospatial Analysis of the Distribution of Public Secondary Education Institutions in the City of Sabha (Libya Journal of Geographical Studies, 2026)
This study aims to clarify the role of Geographic Information Systems (GIS) in analyzing the geospatial distribution of public secondary education institutions in the city of Sabha. This is achieved through spatial analysis and interpretation of the current distribution pattern of these institutions and their relationship with selected geographic variables, particularly population and area. The study also seeks to explain the prevailing geospatial distribution pattern of secondary education institutions. The research adopts the descriptive, quantitative, and analytical approaches, employing several spatial statistical techniques, including standard distance, mean center, weighted mean center, directional distribution, standard deviational ellipse, nearest neighbor index, Moran’s I, and spatial buffering, to examine service coverage in the city of Sabha and assess the extent to which planning standards are met by educational institutions. The results reveal that the geospatial distribution pattern of secondary education institutions is completely clustered and characterized by inequitable distribution and uneven spatial spread across the city. There is a clear concentration in the numerical distribution of secondary education institutions, alongside noticeable variation in the spatial distribution of some of them. This situation is primarily attributed to disparities in population distribution among the urban districts of Sabha. The study also addresses the current and future needs of secondary education institutions, including secondary schools and technical and vocational institutes in the city, based on population projections and national planning standards.
Keywords: Secondary education; upper secondary education; technical and vocational institutes; geospatial distribution; distribution pattern.